Enhancing holistic patient care of black individuals diagnosed with HIV and comorbid chronic conditions - Marc Fleming; Saharnaz Nedjat; Jon C. Schommer; Crystal K. Hodge (Exploratory Research in Clinical and Social Pharmacy)
Background: Pharmacists can play a crucial role in delivering the holistic care model. Research suggests that HIV-positive African American patients particularly benefit from this approach compared to other communities. Typically, pharmacists in community pharmacy settings are limited in their access to a patient's medical record, preventing holistic care delivery. Objectives: This study addressed the impact of access to medical records on a holistic patient care approach among pharmacists engaged in medication therapy management. Methods: This was a sub-analysis of a randomized controlled trial of the impact of community pharmacist access to medical records during MTM for African Americans diagnosed with HIV and multimorbidity with hypertension (HTN) and/or type 2 diabetes mellitus (DM). A random sample was selected of 30 participants (15 in the intervention arm with access to medical records and 15 in the control arm) who completed at least seven study visits between 2019 and 2021. A quantitative content analysis of the study pharmacist visit notes was conducted to identify themes of pharmacist interventions. The percentages of the theme's repetitions were compared across study groups using the Fisher exact test. Results: Thirteen themes were extracted from the pharmacists' visit notes. The intervention group demonstrated a higher repetition of themes concerning any disease, medicine, exercise/weight/diet, sexual, sleeping, smoking, alcohol/marijuana, vaccination, will/power of attorney, food/ housing, and depression/stress. Themes related to career goals and recommending consultation with a provider were repeated more in the control group. The two study groups had statistically significant differences in the percentages of repetition of seven themes. Conclusion: Access to medical records enables pharmacists to focus more on mental health, lifestyle, and social determinants of health.